The Influence of Prayer, Al-Quran Recitation, Physical Exercise, and Holidays on Positive Thinking: Exploring Stress Coping Strategies for Mental Well-Being - Hasin, Hanafiah; Jamil, Anita; Helmy, Herlina; Johari, Yang Chik (Information Management and Business Review, 2024)
This research delves into how prayer practices and recitation of Al Quran, along with activity and holidays, contribute to nurturing perspectives as ways to deal with stress effectively in the workplace setting where job-related stress can significantly impact both personal well-being and productivity within organizations. It is crucial to comprehend and encourage beneficial coping mechanisms in such scenarios. The study investigates the correlation between these coping strategies and positive thinking, recognized for their role in bolstering mental well-being and stress handling. A quantitative cross-sectional approach was employed for this study. Participants filled out questionnaires to measure how often and how much prayer practices like reciting the Al Quran, engaging in exercise, and holidays influenced their outlook on life. Researchers used linear regression analysis to determine how important each activity was in boosting thinking. The results showed that prayer sessions, physical activity, and spending time with family during holidays positively promoted positivity in individuals’ minds; among these activities, holidays seemed to have an effect. However, reciting the Al Quran did not have an impact, based on the analysis of this study. The findings emphasize how adding rituals and hobbies to our routines can boost mental health and help us manage stress better in the long run. This research provides tips for people looking to manage stress and maintain a positive mindset.